2004
DOI: 10.1111/j.1537-2995.2004.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of maternal and neonatal factors that influence the nucleated and CD34+ cell yield for cord blood banking

Abstract: Maternal and neonatal factors appeared to affect CB cell yields. These findings might be useful for efficiently collecting more qualified CB units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
127
4
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(164 citation statements)
references
References 24 publications
30
127
4
2
Order By: Relevance
“…These results are consistent with several previous studies showing that maternal age does not affect either nucleated cells or CD34 + cells (Donaldson et al 1999;Nakagawa et al 2004;George et al 2006;Mancinelli et al 2006). However, focusing on the 1-gravidae alone, the maternal age of 1-gravidae have a slightly positive correlation with the total LD cells (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with several previous studies showing that maternal age does not affect either nucleated cells or CD34 + cells (Donaldson et al 1999;Nakagawa et al 2004;George et al 2006;Mancinelli et al 2006). However, focusing on the 1-gravidae alone, the maternal age of 1-gravidae have a slightly positive correlation with the total LD cells (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Some previous studies described the context of CB banking regarding the cost of CB cell processing and freezing in storage (Sirchia et al 1998(Sirchia et al , 1999Ballen et al 2001;Nakagawa et al 2004). Other previous studies also demonstrated the correlations between the number of nucleated/CD34 + cells and maternal/neonatal factors (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;Askari et al 2005;George et al 2006;Mancinelli et al 2006).…”
Section: Cb Units Collected For Subjectsmentioning
confidence: 91%
See 1 more Smart Citation
“…8,9 Studies performed on healthy pregnancies have shown that gestational and obstetric factors, including maternal age, parity, gestational age, length of labor, stress during labor, route of delivery, technique of UCB collection and positioning of the newborn after delivery can influence the numbers of HSC in UCB obtained after delivery. [10][11][12][13][14] A younger maternal age, shorter gestational age and shorter time from collection to processing were associated with higher CD34 + HSC counts. 14 Neonatal characteristics, including gender and weight of the newborn, may also influence the numbers of HSC in UCB.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] A younger maternal age, shorter gestational age and shorter time from collection to processing were associated with higher CD34 + HSC counts. 14 Neonatal characteristics, including gender and weight of the newborn, may also influence the numbers of HSC in UCB. Bigger babies had higher NCC, more CD34 + cells and colony-forming units granulocyte-macrophage (CFU-GM).…”
Section: Introductionmentioning
confidence: 99%